Inhibition of canalicular and sinusoidal taurocholate efflux by cholestatic drugs in human hepatoma HepaRG cells. (27th October 2022) - Le Vée, Marc; Moreau, Amélie; Jouan, Elodie; Denizot, Claire; Parmentier, Yannick; Fardel, Olivier
Abstract: HepaRG cells are highly‐differentiated human hepatoma cells, which are increasingly recognized as a convenient cellular model for in vitro evaluation of hepatic metabolism, transport, and/or toxicity of drugs. The present study was designed to evaluate whether HepaRG cells can also be useful for studying drug‐mediated inhibition of canalicular and/or sinusoidal hepatic efflux of bile acids, which constitutes a major mechanism of drug‐induced liver toxicity. For this purpose, HepaRG cells, initially loaded with the bile acid taurocholate (TC), were reincubated in TC‐free transport assay medium, in the presence or absence of calcium or drugs, before analysis of TC retention. This method allowed us to objectivize and quantitatively measure biliary and sinusoidal efflux of TC from HepaRG cells, through distinguishing cellular and canalicular compartments. In particular, time‐course analysis of the TC‐free reincubation period of HepaRG cells, that is, the efflux period, indicated that a 20 min‐efflux period allowed reaching biliary and sinusoidal excretion indexes for TC around 80% and 60%, respectively. Addition of the prototypical cholestatic drugs bosentan, cyclosporin A, glibenclamide, or troglitazone during the TC‐free efflux phase period was demonstrated to markedly inhibit canalicular and sinusoidal secretion of TC, whereas, by contrast, incubation with the noncholestatic compounds salicylic acid or flumazenil was without effect. Such data therefore support the use of human HepaRG cells for in vitro predicting drug‐induced liver toxicity (DILI) due to the inhibition of hepatic bile acid secretion, using a biphasic TC loading/efflux assay. Abstract : Effects of cholestatic drugs towards hepatic canalicular and sinusoidal secretion of bile acids were investigated using a biphasic functional assay in human hepatoma HepaRG cells. After an initial loading phase with taurocholate, cells were re‐incubated in taurocholate‐free medium (efflux phase), with or without calcium (for modulating the opening of bile canaliculi) and in the absence or presence of cholestatic drugs. This permitted to simultaneously determine the effects of cholestatic chemicals towards canalicular and sinusoidal secretion of taurocholate.